6 nonsmokers - Abbey, Francis; St. John, Jenna; Tomarchio, Bridgetta; Thompson, Greg (Actor); Murphy, Jim (Actor); Ciscovaras Pictures (Firm); Leomark Studios (Firm) ([Washington, D.C.] : Ciscovaras Pictures, 2011)
Nobel winner Dr. Henry Caldwell, the world's foremost mediator, and his brilliant associate, Dr. Regina Powell, have resolved conflicts ranging from family to international disputes. His latest achievement, The Caldwell Method, is capable of resolving any conflict in 100 days using techniques and strategies he has assembled. His main rival, Dr. John-Michael Robertson, eager to contest Henry's declaration, crashes the Method's unveiling. John-Michael had conducted a study on Non-Familial Domestic Disputes, known as "The Roommate Study," during which he encountered six roommates, known as the "6 Nonsmokers," who cost him students, grants, book deals, and nearly his career. John-Michael's challenge to Henry is to put the Method up against the 6 Nonsmokers and see which one comes out intact.
Originally released as a motion picture in 2013
Bridgetta Tomarchio, Greg Thompson, Jim Murphy, Frank B. Moorman, Ariana Almajan, Danny Gavigan, Demetrius Parker, Kelley Slagle, Jenna St. John.
Cinematographer, Jamie Bender ; editor, Francis Abbey ; music, Noah Potter.
In English; with optional English subtitles.
Winner of the Award of Merit, at the Accolade Competition 2012
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 26, 2018)
Keywords: Smoking -- Drama; Group psychotherapy -- Drama; Problem-solving therapy -- Drama; Interpersonal relations -- Drama; Comedy films; Feature films; Internet videos; Streaming video